2017
DOI: 10.15448/1980-6523.2016.4.21918
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial trauma in a public hospital in Central Brazil: A retrospective study of 405 patients

Abstract: OBJECTIVE: To evaluate epidemiological aspects of maxillofacial injuries in hospitalized patients. METHODS: The sample was composed of 405 patients treated at the Department of Oral and Maxillofacial Surgery of the Emergency Hospital of Aparecida de Goiânia, Brazil, between 2011 and 2013. The following informations were collected from the patients' medical records: gender, age, cause of injury, seasonal distribution and type of injury. The statistical treatment analyzed data from frequency distribution and chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
0
7
0
2
Order By: Relevance
“…Regarding the seasonal distribution, the results showed that most of the cases occurred in the fall (n=89; 25.8%), winter and spring (n=77; 22.2% each). Scartezini et al 4 studied the prevalence of oral maxillofacial injuries in patients treated at the Hospital for urgencies of Aparecida de Goiânia. The authors observed high number of traumas in the fall (38.0%) and summer (34.0%).…”
Section: Continuaçãomentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the seasonal distribution, the results showed that most of the cases occurred in the fall (n=89; 25.8%), winter and spring (n=77; 22.2% each). Scartezini et al 4 studied the prevalence of oral maxillofacial injuries in patients treated at the Hospital for urgencies of Aparecida de Goiânia. The authors observed high number of traumas in the fall (38.0%) and summer (34.0%).…”
Section: Continuaçãomentioning
confidence: 99%
“…It is prudent to highlight that Brazil is a tropical country, where drastic changes of temperature are not observed, in most regions, during the year. This means that all four seasons of the year are not well defined, therefore, the establishment of comparisons among studies conducted in different geographical areas of Brazil and among studies conducted in other countries should be established with care 4 .…”
Section: Continuaçãomentioning
confidence: 99%
See 3 more Smart Citations